Drafting's improvement of 3000-m running performance in elite athletes: is it a placebo effect? - Zouhal, H.; Abderrahman, A. B.; Prioux, J.; Knechtle, B.; Bouguerra, L.; Kebsi, W.; Noakes, T. D. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To determine the effect of drafting on running time, physiological response, and rating of perceived exertion (RPE) during 3000-m track running. Methods: Ten elite middle- and long-distance runners performed 3 track-running sessions. The 1st session determined maximal oxygen uptake and maximal aerobic speed using a lightweight ambulatory respiratory gas-exchange system (K4B2). The 2nd and the 3rd tests consisted of nondrafting 3000-m running (3000-mND) and 3000-m running with drafting for the 1st 2000 m (3000-mD) performed on the track in a randomized counterbalanced order. Results: Performance during the 3000-mND (553.59 ± 22.15 s) was significantly slower (P < .05) than during the 3000-mD (544.74 ± 18.72 s). Cardiorespiratory responses were not significantly different between the trials. However, blood lactate concentration was significantly higher (P < .05) after the 3000-mND (16.4 ± 2.3 mmol/L) than after the 3000-mD (13.2 ± 5.6 mmol/L). Athletes perceived the 3000-mND as more strenuous than the 3000-mD (P < .05) (RPE = 16.1 ± 0.8 vs 13.1 ± 1.3). Results demonstrate that drafting has a significant effect on performance in highly trained runners. Conclusion: This effect could not be explained by a reduced energy expenditure or cardiorespiratory effort as a result of drafting. This raises the possibility that drafting may aid running performance by both physiological and nonphysiological (ie, psychological) effects.